NILAI-NILAI FILSAFAT PIIL PESENGGIRI DALAM PANTUN NYEKHAHKON MAJU - Muntazir, Muntazir (JURNAL PESONA, 2018)
AbstractPiil Pesenggiri is the life philosophy of Lampung society. The purpose of this study is to describe the values of Piil Pesenggiri in Pantun Nyekhahkon Maju. Pantun nyekhahkon maju  is one of the rhymes conveyed in the procession of nyambai activity by the indigenous people of Saibatin  in West Lampung. Qualitative method is characteristic of this research. The object of this research is the written verbal word in the form of pantun. Oral analysis technique is stylistic study that is about meaning and function. From the results of data analysis obtained the description of the content of Piil Pesenggiri values in the nykhahkon pantun, first, the whole contents of the pantun illustrates the philosophy Piil Persenggiri detailed in the supporting points. Second,  bejuluk beadek, the family dream can be achieved with hard work. Third, nemui nyimah, which is the behavior of politeness is the key to the success of social life. Fourth nengah nyappur namely, in married life must be good at respecting fellow, support and tolerance. The fifth, sakai sambaian, which is signed  by mutual cooperation in solving all problems.Keywords: values, piil pesenggiri, pantun nykhahkon maju